Development of a recommendation model for information technology-based college study program options for high school students - Triyanto, Agus; Setiani, Ismarini Bekti; Sari, Widya Juwita; Peng, Yang (Universitas Negeri Yogyakarta, 2023)
Students who plan to attend university frequently struggle with making decisions. The challenge of students' decision-making regarding study program selection in higher education arises from factors such as self-understanding, including intelligence, talents, and interests, as well as understanding of the educational environment and available information on study programs. The objective of this research is to create a recommendation model for high school students in Yogyakarta to choose information technology-based study programs. A model is employed to aid guidance and counseling teachers in offering guidance to high school students regarding their choice of study programs in higher education. This guidance is based on the students' self-awareness and understanding of their surroundings. The research described in this study follows the Borg and Gall model, which consists of 10 development steps in the field of research and development (R&D). Data on the RPP-PT Model was obtained through questionnaires and interview guides. Data analysis involves the utilization of both quantitative and qualitative methods for analyzing data. The study presents a recommendation model for choosing information technology-based study programs in higher education. This model is designed to provide guidance and counseling teachers with recommendations for college study program choices based on students' learning achievement, general abilities, talents, and interests. External factors, including parental expectations, should be taken into account when considering future development.